Perkawinan Beda Agama Perspektif Majelis Ulama Indonesia dan Muhammadiyah - Ibad, Mifatakhul Bil (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
This article discusses interfaith marriage law according to the fatwa of the Indonesian Ulema Council and Muhammadiyah. According to the MUI’s fatwa, interfaith marriages are unlawful with the proposition of chapter of al-Baqarah verse 221. While Muhammadiyah believes interfaith marriages are permissible on the basis of al-Maidah verse 5. MUI forbids interfaith marriages because it can lead to conflicts between Muslims and cause unrest in the community. Muhammadiyah allows interfaith marriages because in Islamic history it is known that the Prophet Muhammad was married to a Christian woman from Egypt, namely Maria al-Qibthiyyah. Some of the Companions of the Prophet also married the women of the Book. MUI equates ahlu al-Kitab (Nashrani and Jewish) including the category of polytheists, while Muhammadiyah considers that women from ahlu al-Kitab does not include polytheists as stated in chapter al-Baqarah verse 221. This is because according to Muhammadiyah there are many verses that distinguish between ahlu al-Kitab and polytheism by considering the linguistic analysis in chapter al-Baqarah verse 105 and al-Bayyinah verse 1. [Artikel ini membahas tentang hukum perkawinan beda agama menurut fatwa Majelis Ulama Indonesia dan Muhammadiyah. Menurut fatwa MUI, perkawinan beda agama adalah haram dengan dalil surat alBaqarah ayat 221. Sedangkan Muhammadiyah beranggapan peerkawinan beda agama adalah boleh dengan dasar surat al-Maidah ayat 5. MUI mengharamkan perkawinan beda agama karena hal tersebut bisa menimbulkan konflik antar sesama umat Islam dan mengakibatkan keresahan di masyarakat. Muhammadiyah membolehkan perkawinan beda agama karena dalam sejarah Islam diketahui bahwa Nabi Muhammad Saw pernah menikah dengan seorang wanita Nasrani yang berasal dari Mesir, yaitu Maria al-Qibthiyyah. Beberapa sahabat Nabi juga menikah dengan wanita-wanita ahlu al-Kitab. MUI menyamakan ahlu al-Kitab (Nashrani dan Yahudi) termasuk kategori musyrik, sedangkan Muhammadiyah beranggapan bahwasanya wanita ahlu al-Kitab itu tidak termasuk musyrikat sebagaimana yang tercantum dalam surat al-Baqarah ayat 221. Hal tersebut disebabkan menurut Muhammadiyah banyak ayat yang menbedakan antara ahlu al-Kitab dengan musyrik dengan mempertimbangkan analisis kebahasaan dalam surat al-Baqarah ayat 105 dan al-Bayyinah ayat 1.]